Distribution pattern of soil fungi community diversity in alpine meadow in Qilian Mountains of eastern Qinghai-Tibetan Plateau - Qiang Li; Guoxing He; Tong Wen; Degang Zhang; Xiaoni Liu (Ecological Indicators, 2022)
The distribution pattern and maintenance mechanism of fungal biodiversity in altitude and aspect have been a research hotspot of biodiversity and ecosystem functions. Based on high-throughput sequencing, this research analyzed the composition, diversity and function of soil fungal communities in alpine meadows at different altitudes (i.e., 2800, 3000, 3200, 3400, 3600, 3800, and 4000 m) and aspects (sunny aspect and shady aspect), as well as the relationship between these soil fungal communities and environmental factors. The results showed that, with the rising altitude, the Shannon and Chao1 index of soil fungi first increased and then decreased. Moreover, at the same altitude, except at 3800 m and 4000 m altitude, the Shannon index and Chao1 index in sunny aspect were higher than those in shady aspect. The NMDS-based analysis could distinguish fungal communities at different altitudes and aspects, indicating that the characteristics of soil fungal communities varied significantly with changing altitude and aspect. In the study area, Basidiomycota, Ascomycota and Mortierellomycota were the dominant phyla, while Agaricomycetes, Dothideomycetes and Archaeorhizomycetes were the dominant class, which presented significant differences at different altitudes and aspects. A total of 167 fungi species at different classification levels in the study area were analyzed by LEfSe. FUNGuild analysis identified that soil fungi were mainly divided into eight ecological functional groups, mainly Ectomycorrhizal- Orchid_Mycorrhizal- Root_Associated _Biotroph and Undefined_ Saprotroph. The AGB, SOC, TN and SWC were the main factors affecting the fungal community. In conclusion, altitude and aspect significantly changed the composition and diversity of fungal communities.